Simulasi Pengukuran Suhu dan Kelembaban Ruangan Menggunakan Arduino Uno dan DHT22 pada Wokwi - Anggie Maulia; Naif Baihaqi; Nur Fajri Faiz; Muhammad Rizki; Didik Aribowo (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
This study simulates a temperature and humidity monitoring system using the DHT22 sensor virtually on the Wokwi platform. The research background highlights the importance of monitoring temperature and humidity to maintain environmental conditions automatically, offering greater efficiency than manual monitoring. The study aims to test the functionality of devices and program codes without requiring physical hardware. The methods include literature review, software design, circuit schematic arrangement, and simulations with temperature and humidity parameters. Simulation results indicate the system can accurately measure temperature and humidity, display data on the LCD, and activate the relay and LED if the temperature exceeds 25°C. This research provides a foundation for developing automatic monitoring systems beneficial in daily life.